Endogenous Expression of the Human CD83 Attenuates EAE Symptoms in Humanized Transgenic Mice and Increases the Activity of Regulatory T Cells - Zinser, Elisabeth; Naumann, Ronald; Wild, Andreas; Michalski, Julia; Deinzer, Anja; Stich, Lena; Kuhnt, Christine; Steinkasserer, Alexander; Knippertz, Ilka (Frontiers in Immunology, 2019)
The CD83 is a type I membrane protein and part of the immunoglobulin superfamily of receptors. CD83 is involved in the regulation of antigen presentation and dendritic cell dependent allogeneic T cell proliferation. A soluble form of CD83 inhibits dendritic cell maturation and function. Furthermore, CD83 is expressed on activated B cells, T cells, and in particular on regulatory T cells. Previous studies on murine CD83 demonstrated this molecule to be involved in several immune-regulatory processes, comprising that CD83 plays a key role in the development and function of different immune cells. In order to get further insights into the function of the human CD83 and to provide preclinical tools to guide the function of CD83/sCD83 for therapeutic purposes we generated Bacterial Artificial Chromosomes (BAC) transgenic mice. BACs are excellent tools for manipulating large DNA fragments and are utilized to engineer transgenic mice by pronuclear injection. Two different founders of BAC transgenic mice expressing human CD83 (BAC-hCD83(tg) mice) were generated and were examined for the hCD83 expression on different immune cells as well as both the in vitro and in vivo role of human CD83 (hCD83) in health and disease. Here, we found the hCD83 molecule to be present on activated DCs, B cells and subtypes of CD4(+) T cells. CD8(+) T cells, on the other hand, showed almost no hCD83 expression. To address the function of hCD83, we performed in vitro mixed lymphocyte reactions (MLR) as well as suppression assays and we used the in vivo model of experimental autoimmune encephalomyelitis (EAE) comparing wild-type and hCD83-BAC mice. Results herein showed a clearly diminished capacity of hCD83-BAC-derived T cells to proliferate accompanied by an enhanced activation and suppressive activity of hCD83-BAC-derived Tregs. Furthermore, hCD83-BAC mice were found to recover faster from EAE-associated symptoms than wild-type mice, encouraging the relevance also of the hCD83 as a key molecule for the regulatory phenotype of Tregs in vitro and in vivo.
CRIS-Team WoS Importer:2019-07-12

Environment affects dendritic cells' response via Aryl Hydrocarbon Receptor ligands: a comparison between endogenous and exogenous ligands - Sadeghi Shermeh, Atefeh; Wild, Andreas; Michalski, Julia; Steinkasserer, Alexander (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Quercetin induces an immunoregulatory phenotype in maturing human dendritic cells - Michalski, Julia; Deinzer, Anja; Stich, Lena; Zinser, Elisabeth; Steinkasserer, Alexander; Knippertz, Ilka (Immunobiology, 2020)
The aryl hydrocarbon receptor (AhR) is an environmental sensor and ligand-activated transcription factor that is critically involved in the regulation of inflammatory responses and the induction of tolerance by modulating immune cells. As dendritic cells (DCs) express high AhR levels, they are efficient to induce immunomodulatory effects after being exposed to AhR-activating compounds derived from the environment or diet. To gain new insights into the molecular targets following AhR-activation in human monocyte-derived (mo)DCs, we investigated whether the natural AhR ligand quercetin or the synthetic ligand 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) modulates the function of human moDCs regarding their capability to prime naïve T cells or to migrate. As only quercetin, but not TCDD, impaired T cell activation and migration of LPS-matured DCs (LPS-DCs), we analyzed the mode of action of quercetin on moDCs in more detail. Here, we found a specific down-regulation of the immunomodulatory molecule CD83 through the direct binding of the activated AhR to the CD83 promoter. Furthermore, treatment of LPS-DCs with quercetin resulted in a reduced production of the pro-inflammatory cytokine IL-12p70 and in an increased expression of the immunoregulatory molecules disabled adaptor protein (Dab) 2, immunoglobulin-like transcript (ILT)-3, ILT4, ILT5 as well as ectonucleotidases CD39 and CD73, thereby inducing a tolerogenic phenotype in quercetin-treated maturing DCs. Overall, these data demonstrate that quercetin represents a potent immunomodulatory agent to alter human DC phenotype and function, shifting the immune balance from inflammation to resolution.
CRIS-Team Scopus Importer:2020-03-10
Keywords: Aryl hydrocarbon receptor; Dendritic cells; Quercetin; Regulatory T cells; TCDD; Tolerance